1997
DOI: 10.2135/cropsci1997.0011183x003700020031x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Control of Soybean Seed Storage Protein

Abstract: There is interest in increasing the protein concentration of soybean [Glycine max (L.) Merr.] seed. Potentially, this could change its protein composition and perhaps its value as a livestock feed. Our objective was to examine the change in protein composition of soybean seed with change in protein concentration as influenced by nitrogen source supplied. ‘Harper’ soybean was grown in hydroponic culture and supplied with different nitrogen sources (KNO3, NH4NO3N2, urea) during pod filling. Protein quality was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
70
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 0 publications
5
70
0
1
Order By: Relevance
“…For those grown on mineral N, the seed contained increasingly greater protein concentration with increasing proportion of nitrogen supplied in the reduced form. Paek et al (1997) analyzed the seed produced from these treatments to investigate how change in seed protein concentration, independent of genotype, changes seed protein composition. The results of two experiments were consistent in showing that raising soya bean seed protein concentration through enhanced plant N simulation results in poorer protein quality (Fig 3).…”
Section: Variation In Total Seed Protein Compositionmentioning
confidence: 99%
“…For those grown on mineral N, the seed contained increasingly greater protein concentration with increasing proportion of nitrogen supplied in the reduced form. Paek et al (1997) analyzed the seed produced from these treatments to investigate how change in seed protein concentration, independent of genotype, changes seed protein composition. The results of two experiments were consistent in showing that raising soya bean seed protein concentration through enhanced plant N simulation results in poorer protein quality (Fig 3).…”
Section: Variation In Total Seed Protein Compositionmentioning
confidence: 99%
“…A similar phenomenon was noted in barley where a sulfur poor storage protein increased at a greater rate than a sulfur-rich protein with increasing seed protein concentration (Giese et aL, 1983;Giese and Hopp, 1984). Paek et al (1997) speculated that inability of the soybean seed to increase glycinin concentrations in parallel with P-conglycinin, may be due to a limitation in S availability to the developing seed. Increased protein production in the seed through increased nitrogen availability may dilute the otherwise high quality glycinin proteins by production of the (5 subunit, if S supply is not increased concurrently.…”
mentioning
confidence: 56%
“…Paek et al (1997) found nitrogen deficiency (here administered by allowing soybean to use Na fixation as its sole source of N) to reduce the total quantity of each subunit of both glycinin and P-conglycinin. The reduction in accumulation of these proteins was not uniform, however.…”
Section: Utilization Of S Witiiin Tiie Seedmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the accumulation of f3-conglycinin, especially the f3-subunit was positively correlated with the seed total nitrogen concentration (Ohtake at al. 1996;Peak et al 1997). Gayler and Sykes (1985) reported that sulfur deficiency led to a decrease in the level of glycinin, and an increase in the level of f3-conglycinin.…”
mentioning
confidence: 99%